Shipping Information System in Distribution Warehouses Using a Web-Based Barcode System - Dony Samara; Mushlihudin Mushlihudin (Universitas Ahmad Dahlan, 2020)
One of the data in the industrial process is information on shipping goods in a distribution warehouse. This study proposes a web-based freight information system in a distribution warehouse with a barcode system as the naming management of goods. The barcode reading system uses a barcode scanner as a barcode label reader, with an Arduino microcontroller device and NodeMCU as a controller and communication device with the web. The localhost web-based information system was built using the XAMPP application. Display information system using a simple display on the browser page. The results obtained in this study have successfully built a barcode-based goods delivery management system, information about the goods is coded into a barcode. The barcode reading system has successfully read and communicated with the web, with experiments conducted using 100 barcode labels, the success of reading and sending data has shown good results. Goods delivery information system in a web-based distribution warehouse has also been successfully built with an average data storage time of 5.5 seconds.Salah satu data dalam proses industri yaitu informasi pengiriman barang di gudang distribusi. Penelitian ini mengusulkan sebuah sistem informasi pengiriman barang berbasis web di sebuah gudang distribusi dengan sistem barcode sebagai manajemen penamaan barang. Sistem pembacaan barcode menggunakan barcode scanner sebagai pembaca label barcode, dengan perangkat mikrokontroler Arduino dan NodeMCU sebagai perangkat kontroler dan komunikasi dengan web. Sistem informasi berbasis web localhost dibangun menggunakan aplikasi XAMPP. Tampilan sistem informasi menggunakan tampilan sederhana di halaman browser. Hasil yang didapatkan dalam penelitian ini adalah telah berhasil dibangun sistem manajemen pengiriman barang berbasis barcode, informasi mengenai barang dikodekan kedalam bentuk barcode. Sistem pembacaan barcode telah berhasil membaca dan berkomunikasi dengan web, dengan percobaan yang dilakukan menggunakan 100 label barcode keberhasilan pembacaan dan pengiriman data telah menunjukkan hasil yang baik. Sistem informasi pengiriman barang di gudang distribusi berbasis web telah berhasil pula dibangun dengan lama penyimpanan data rata – rata 5,5 detik.